Vitamin E improves the reproductive system of male rats exposed to busulfan chemotherapy: Vitamin E improves male rat fertility post-busulfan - Kadhim, Ameer Hameed; El Arbi, Mehdi; Muhammed , Hayder Ali (Cellular and Molecular Biology, 2025)
Vitamin E is a well-known antioxidant and is frequently used as an adjunct treatment in cancer therapy. Busulfan is a commonly used drug for cancer treatment. In this study, twenty-eight male rats, ten weeks old and weighing between 250 and 300 grams, were divided into four groups. The first group served as the control and received daily intraperitoneal injections of Dimethyl sulfoxide (DMSO) for four weeks. The second group received a single dose of Busulfan at 40 mg/kg body weight via intraperitoneal injection. The third group received the same single dose of Busulfan along with daily intraperitoneal injections of Vitamin E at 100 mg/kg body weight for four weeks. The fourth group was given only Vitamin E at the same dosage for four weeks. At the end of the experiment, the animals were sacrificed, and blood samples were collected to test antioxidant enzyme levels (GSH, SOD, CAT) and analyze serum concentrations of reproductive hormones (FSH, LH, and testosterone). Additionally, sperm motility and viability were assessed after collecting epididymal spermatozoa. The findings revealed that Busulfan significantly increased serum levels of both FSH and LH while causing a notable decrease in testosterone levels. Furthermore, Busulfan treatment resulted in a significant reduction in sperm count, motility, and viability, along with a marked increase in sperm morphological abnormalities. In contrast, supplementation with Vitamin E alongside Busulfan improved hormone levels and enhanced sperm function. In conclusion, Busulfan has a toxic effect on sperm and directly impacts body weight and testicular weight. However, Vitamin E demonstrates beneficial therapeutic effects on testicular tissue and enhances sperm production in rats treated with Busulfan.